1985
DOI: 10.1002/zaac.19855280910
|View full text |Cite
|
Sign up to set email alerts
|

Zum Kondensationsverhalten von Silanolen. I. Kondensation von Trimethylsilanol

Abstract: An Trimethylsilanol als Modellverbindung wurden Möglichkeiten untersucht, die Silanol‐Kondensation mit Hilfe der Gaschromatographie, der 1H‐NMR‐ bzw. der IR‐Spektroskopie zu verfolgen. Es wurden kinetische Daten erhalten für die sauer und die basisch katalysierte Kondensation in wäßrigem Dioxan und in Toluen/Wasser.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
3

Year Published

1986
1986
2005
2005

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 3 publications
0
7
0
3
Order By: Relevance
“…Previously, it has been suggested that silanol homocondensation should be first order with respect to silanol and first order with respect to hydroxide anion. 14 This is actually a simplification of eq 20 and 21 when K d is large enough and [H 2 O] is small enough that [SiO -] ∼ [NaOH] 0 at all times. Keeping the water content low is easy to do when one starts with silanols and works in nonalcoholic solvents.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, it has been suggested that silanol homocondensation should be first order with respect to silanol and first order with respect to hydroxide anion. 14 This is actually a simplification of eq 20 and 21 when K d is large enough and [H 2 O] is small enough that [SiO -] ∼ [NaOH] 0 at all times. Keeping the water content low is easy to do when one starts with silanols and works in nonalcoholic solvents.…”
Section: Resultsmentioning
confidence: 99%
“…We might anticipate that this should be true regardless of the condensation route and Figure 3 gives no cause to doubt this. This dependence is easily explained by the following classic scheme: 14,20 where S represents a proton-accepting solvent (either ethanol or water) and X is either a hydrogen or an ethyl group.…”
Section: Resultsmentioning
confidence: 99%
“…Wie bereits fur die basenkatalysierte Kondensation von Trimethylsilanol in Wasser beschrieben wurde [ 7 ] , ergibt sich auch fur die Reaktion in Dioxan/ Wasser ein Geschwindigkeitsgesetz (I), in das die Silanol-und die Katalysatorkonzentration mit jeweils erster Ordnung eingehen.…”
Section: K I N E T I S C H E D a T E Nunclassified
“…entspricht wegen des weit auf der Seite des Silanolats befindlichen Gleichgewichts (4) und der damit gultigen Aussage (7) c(Si0-) = c,, (Kat.) (7) dem experimentell gefundenen Geschwindigkeitsgesetz (1). G l e i c h g e w i c h t s k o n s t a n t e n u n d S i l o x a n s p a l t u n g Aus den sich einstellenden Gleichgewichtskonzentrationen an Silanol und entsprechendem Siloxan wurden auch fur die basenkatalysierte Kondensation die Gleichgewichtskonstanten K ermittelt.…”
Section: K I N E T I S C H E D a T E Nunclassified
“…Bei direkter Umsetzung der Siloxanole mit Trimethylsilanol wird die kinetische Auswertung durch die bevorzugt ablaufende Eigenkondensation des Trimethylsilanols erschwert . Deshalb wurde die Reaktion in der ublichen Dioxan/ SiOH) kannten Gleichgewichtskonstante fur HexamethyldisiloxanlTrimethylsilanol (K = 130)[5] berechnete Trimethylsilanol-Konzentration kann zur Berechnung von k berucksichtigt werden. In Tab.…”
unclassified